Helicobacter pylori infection contributes to placental impairment in preeclampsia: basic and clinical evidences. Issue 2 (3rd August 2016) - Di Simone, Nicoletta; Tersigni, Chiara; Cardaropoli, Simona; Franceschi, Francesco; Di Nicuolo, Fiorella; Castellani, Roberta; Bugli, Francesca; de Waure, Chiara; Cavaliere, Anna Franca; Gasbarrini, Antonio; Sanguinetti, Maurizio; Scambia, Giovanni; et al.
Abstract: Background: Preeclampsia (PE) is a major cause of maternal and neonatal morbidity and mortality. Epidemiological association between Helicobacter pylori (Hp) infection and PE onset has been widely shown. The aim of this study was to analyze a possible correlation between Hp infection and the severity of clinical presentation of PE and to identify an immunologic mechanism triggered by Hp infection potentially contributing to the pathogenesis of PE. Materials and Methods: Sera from 93 preeclamptic women and 87 healthy pregnant women were tested for Hp infection by immunoassay and for anti‐CagA antibodies by Western blot assay. The serologic results were correlated with the clinical features of PE. The functional effect of serum IgG fractions, positive or negative for Hp, from preeclamptic women or controls were tested on trophoblast and endothelial cell cultures and in a murine model of angiogenesis. Results: Preeclamptic women showed higher seroprevalence of Hp infection (57.0%) compared to controls (33.3%) ( P <.001). The seropositivity for CagA‐positive strains of Hp was 45.2% in preeclamptic women vs 13.7% in controls ( P <.001). In PE women, Hp infection was associated with abnormality of uterine arteries Doppler ( P <.001). Hp+ IgG fractions from preeclamptic women bound to trophoblast and endometrial endothelial cell cultures, reducing in vitro invasiveness and angiogenesis, respectively, and inhibited angiogenesis in mice. Conclusions: Our data show, for the first time, an association between Hp infection and PE with abnormal uterine arteries Doppler velocimetry, suggesting a role for Hp infection in impairing placental development and increasing the risk to develop PE. This study opens the new perspective of a potential screening and treatment for Hp infection in pregnancy.